Sikap Toleransi dalam Membangun Harmoni Sosial di Kalangan Mahasiswa dan Dosen Binus University - Huang Mei Thieng; Chalysta Kezia Sodikim; Estella Nelvina; Fillipus Manson; Aryusmar; Heru Widoyo (PT. AHLAL PUBLISHER NUSANTARA, 2025)
This study explores the role of interfaith dialogue as a strategic approach to strengthening social harmony within pluralistic communities. The background of this research lies in the increasing tension, misunderstanding, and prejudice among groups that differ in religious identity, which often escalates into social conflict. The objective of this study is to describe how interfaith dialogue contributes to tolerance-building, conflict mitigation, and the creation of inclusive social spaces. The research employs a qualitative descriptive method supported by literature studies. The findings indicate that interfaith dialogue is effective in reducing negative perceptions, expanding mutual understanding, and reinforcing collective commitment to peace. This study also confirms that strengthening dialogue at the community level aligns with SDG 16, which emphasizes peace, justice, and strong institutions. The results highlight that dialogue-based initiatives—especially when involving youth, religious leaders, and community organizations—significantly contribute to building resilient and harmonious communities. Keywords: dialogue; harmony; interfaith tolerance; peacebuilding; SDG 16 Abstrak. Penelitian ini membahas peran dialog antarumat beragama sebagai pendekatan strategis dalam memperkuat harmoni sosial di tengah masyarakat yang plural. Latar belakang penelitian ini berangkat dari meningkatnya ketegangan, prasangka, dan kesalahpahaman antar kelompok berbeda agama yang berpotensi memicu konflik sosial. Tujuan penelitian ini adalah menggambarkan bagaimana dialog antaragama berkontribusi dalam membangun toleransi, mengurangi konflik, serta menciptakan ruang sosial yang inklusif. Penelitian ini menggunakan metode deskriptif kualitatif dengan dukungan studi literatur. Hasil penelitian menunjukkan bahwa dialog antaragama efektif dalam menurunkan persepsi negatif, memperluas pemahaman bersama, dan memperkuat komitmen kolektif terhadap perdamaian. Studi ini juga menegaskan bahwa penguatan dialog pada tingkat komunitas selaras dengan SDG 16 yang menekankan perdamaian, keadilan, dan institusi yang tangguh. Temuan menunjukkan bahwa inisiatif berbasis dialog—khususnya yang melibatkan pemuda, tokoh agama, dan organisasi masyarakat—berkontribusi signifikan terhadap pembangunan masyarakat yang tangguh dan harmonis. Kata kunci: dialog; harmoni; toleransi antaragama; pembangunan perdamaian; SDG 16